Hip pinning... An historical perspective - Cable, Kim (Operating Room Nurses Association of Canada Journal, 1989)
"We come into the world under the brim of the pelvis and go out through the neck of the femur".1 This quotation conveys the pessimism regarding treatment of hip fractures. There have been a number of important milestones in hip-pinning as a method of dealing with hip fractures. This submission will take a look at these milestones, as well as examine the various catalysts which initiated the procedure and subsequent improvements.